2018
DOI: 10.1002/bjs.10755
|View full text |Cite
|
Sign up to set email alerts
|

Baseline factors predicting a response to neoadjuvant chemotherapy with implications for non-surgical management of triple-negative breast cancer

Abstract: The presence of microcalcifications on imaging and DCIS on initial CNB are associated with residual disease after neoadjuvant chemotherapy in TNBC. These variables can aid in identifying patients with TNBC suitable for inclusion in trials evaluating non-surgical management after neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
(58 reference statements)
1
18
0
4
Order By: Relevance
“…This is consistent with existing evidence that comedo-type, casting and pleomorphic microcalcifications on initial mammography are associated with poorer prognosis [2226]. Interestingly, in contrast to two recent studies, we found no correlation between microcalcification and poorer response to NACT in the TN cancers [7, 8]. This may be due to the differing definitions of complete response; whilst in our study pCR is considered the absence of invasive disease the previous studies considered complete response to be the absence of both invasive and in-situ disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with existing evidence that comedo-type, casting and pleomorphic microcalcifications on initial mammography are associated with poorer prognosis [2226]. Interestingly, in contrast to two recent studies, we found no correlation between microcalcification and poorer response to NACT in the TN cancers [7, 8]. This may be due to the differing definitions of complete response; whilst in our study pCR is considered the absence of invasive disease the previous studies considered complete response to be the absence of both invasive and in-situ disease.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence pertaining to baseline ultrasound and mammography, however, remains scant. Two recent papers considered triple negative cancers alone; one study of 328 patients found the presence of microcalcification on the initial mammogram was significantly associated with residual disease (presumed to include in-situ disease) [7]. A further study comparing tumours that completely responded to tumours with residual in-situ disease following NACT found that the absence of mammographic microcalcification, round shape and posterior enhancement on baseline ultrasound were significantly more common amongst tumours which demonstrated pCR with no residual in-situ disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed better pCR rates for patients with accompanying DCIS ranging from 28 to 36%. [22][23][24][25] The lower pCR rates Another controversial discussion focuses on which tumor stages and tumor biology should be considered for risk-adaptive breast cancer surgery as well as on how to integrate surgical treatment of the axilla. Current research has shown that TNBC or HER2?…”
Section: Discussionmentioning
confidence: 99%
“…Literature is limited regarding the utility of baseline imaging features to predict response to NAC or survival outcomes in breast cancer. A study involving patients with triple-negative breast cancer (TNBC) analyzing clinic-pathological factors, found that the presence of microcalcifications on baseline imaging was associated with predicting residual disease as opposed to patients with pCR [ 29 ]. Radiogenomics involves the integration of imaging characteristics with molecular information and has shown promising results in breast cancer using baseline MRI features [ 30 ].…”
Section: Discussionmentioning
confidence: 99%